BGer 2C 6/2012 vom 13. April 2012 - Bundesgericht (2012)
Direkte Bundessteuer 2007 [2C_9/2012] Staatssteuer 2006 [2C_6/2012] Direkte Bundessteuer 2006 [2C_7/2012] Staatssteuer 2007 [2C_8/2012] | Öffentliche Finanzen & Abgaberecht